Innovative Use of Plastic for a Clean and Sustainable Environmental Management: Learning Cases from Ghana, Africa - Debrah, Justice Kofi; Vidal, Diogo Guedes; Dinis, Maria Alzira Pimenta (Urban science, 2021)
Addressing the plastic problem requires rigorous attention and practical education for sustainability. Due to the common effective waste management practices in some parts of the world, the plastics’ menace is generally well recognized and controlled worldwide. However, some developing countries do not have acceptable waste management practices, resulting in significant environmental, social, and health cross-cutting issues. Plastic is a significant threat to the environment in Ghana, specifically the urban environment and oceans. The new paradigm shift of virtually using non-biodegradable plastics in all daily products sold increases plastic waste in the environment, which creates problems, such as choked drainage system and breeding places for insects. The scale of these issues requires innovative and practical ideas to help solve this problem. The paper shows how plastic waste is innovatively and creatively converted to artifacts and pavement blocks in Ghana. These innovative ideas have contributed to reduce the volume of plastic waste and enhance environmental sustainability in Africa. The community’s benefits involving friendly environmental activities are identified and represent learning cases from Ghana to the world, particularly to Africa.